2022
DOI: 10.1038/s41598-022-06865-6
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor-BB regenerates functional periodontal ligament in the tooth replantation

Abstract: Tooth ankylosis is a pathological condition of periodontal ligament (PDL) restoration after tooth replantation. Platelet-derived growth factor-BB (PDGF-BB) has been proposed as a promising factor for preventing tooth ankylosis. Using rat tooth replantation model, we investigated whether PDGF-BB accelerates the repair of PDL after tooth replantation without ankylosis, and its molecular mechanisms. In PDGF-BB pretreated replanted teeth (PDGF-BB group), ankylosis was markedly reduced and functionally organized PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…In pretreatment with BPs and PDGF‐BB, the mechanical strength increased to 67% and 76% of the control value, respectively. The extensibility, stiffness, and toughness of PDL tissue also increased in both treatments, suggesting their beneficial roles in recovering functional property and preventing ankylosis (Komatsu et al, 2022; Shibata et al, 2004).…”
Section: Approaches To Prevent Ankylosis and Root Resorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pretreatment with BPs and PDGF‐BB, the mechanical strength increased to 67% and 76% of the control value, respectively. The extensibility, stiffness, and toughness of PDL tissue also increased in both treatments, suggesting their beneficial roles in recovering functional property and preventing ankylosis (Komatsu et al, 2022; Shibata et al, 2004).…”
Section: Approaches To Prevent Ankylosis and Root Resorptionmentioning
confidence: 99%
“…In a rat replantation model, we recently showed that the topical application of PDGF‐BB to the root can effectively inhibit tooth ankylosis, which occurs frequently in control replantation. In PDGF‐BB‐pretreated replanted teeth, functionally organized PDL collagen fibers are restored, and the effects of PDGF‐BB on blocking ankylosis are mediated through the suppression of Wnt signaling (Komatsu et al, 2022).…”
Section: Approaches To Prevent Ankylosis and Root Resorptionmentioning
confidence: 99%
“…In periodontal tissue engineering, several growth and differentiation factors, including platelet‐derived growth factors (PDGFs), insulin‐like growth factors (IGFs), fibroblast growth factors (FGFs), transforming growth factor‐β (TGF‐β), enamel matrix protein, and bone morphogenetic proteins (BMPs) have been identified as potential therapeutic candidates to promote healing/regeneration of periodontal defects. PDGFs are mainly secreted by platelet alpha granules, besides platelets, macrophages, fibroblasts, myocytes, endothelial cells, and bone marrow hematopoietic cells also secrete PDGFs (Komatsu, Ideno, Shibata, Nakashima, & Nifuji, 2022). PDGFs exert their biological effects by binding to cell‐surface receptors (PDGFαR and ‐βR) with intrinsic tyrosine kinase activity that induce cells to undergo mitosis, chemotaxis, or matrix synthesis (Lee et al, 2000; Ripamonti, Crooks, Petit, & Rueger, 2001).…”
Section: Regeneration Of Periodontal Tissuesmentioning
confidence: 99%
“…PDGFs exert their biological effects by binding to cell‐surface receptors (PDGFαR and ‐βR) with intrinsic tyrosine kinase activity that induce cells to undergo mitosis, chemotaxis, or matrix synthesis (Lee et al, 2000; Ripamonti, Crooks, Petit, & Rueger, 2001). In vitro experiments have shown that PDGF‐BB significantly increases the ALP activity of osteoblasts, as well as fibroblasts from PDL, cultured on collagen membrane (Komatsu et al, 2022). In a rat alveolar bone defect model, functionally graded material (a clinically available collagen membrane electrospun by a nanofibrous layer on the inner or outer surface) loaded with PDGF on the surface accelerates the regeneration of alveolar bone defect (Joshi, Padhye, & Gupta, 2019).…”
Section: Regeneration Of Periodontal Tissuesmentioning
confidence: 99%
“…It comprises different, histologically defined tissues, i.e., the gingiva, the periodontal ligament (PDL), cementum, and the alveolar bone. Gingival fibroblasts (GFs) and gingival keratinocytes (GKs) are the main constituents of the gingiva, while the PDL, among other tissues, harbors specialized fibroblasts called periodontal ligament fibroblasts (PDLFs) and periodontal ligament stem cells (PDLSCs) [1][2][3][4]. The cementum is populated by cementoblasts, and the alveolar bone consists of osteoblasts, osteoclasts, mesenchymal stem cells (MSCs), and an organic as well as an inorganic matrix [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%